Modelling microbial health risk of wastewater reuse: A systems perspective. (November 2015) - Beaudequin, Denise; Harden, Fiona; Roiko, Anne; Stratton, Helen; Lemckert, Charles; Mengersen, Kerrie
Abstract: There is a widespread need for the use of quantitative microbial risk assessment (QMRA) to determine reclaimed water quality for specific uses, however neither faecal indicator levels nor pathogen concentrations alone are adequate for assessing exposure health risk. The aim of this study was to build a conceptual model representing factors contributing to the microbiological health risks of reusing water treated in maturation ponds. This paper describes the development of an unparameterised model that provides a visual representation of theoretical constructs and variables of interest. Information was collected from the peer-reviewed literature and through consultation with experts from regulatory authorities and academic disciplines. In this paper we explore how, considering microbial risk as a modular system, following the QMRA framework enables incorporation of the many factors influencing human exposure and dose response, to better characterise likely human health impacts. By using and expanding upon the QMRA framework we deliver new insights into this important field of environmental exposures. We present a conceptual model of health risk of microbial exposure which can be used for maturation ponds and, more importantly, as a generic tool to assess health risk in diverse wastewater reuse scenarios. Graphical abstract: Highlights: We present a new model of microbial risk related to wastewater reuse. Influences on pathogen density, exposure pathway and dose–response are explored. Model provides a generic tool to assess health risk in diverse water use scenarios.